Challenges to managing quality of care in northern Queensland residential aged care facilities. Issue 1 (2022) - Dawes, Nathan; Topp, Stephanie M.
Abstract: Background: Senior management teams in residential aged care facilities (RACFs) face a range of challenges in providing quality health care services. With increasing attention directed at quality problems in Australian RACFs, there is an urgent need to better understand the experiences of this crucial cadre. This qualitative study sought to identify challenges from the perspective of current senior managers in residential aged care (RAC) organisations and map their influence on the quality of health care provided within. Methods: 20 semi-structured interviews were conducted with senior managers in 14 RACFs in northern Queensland, Australia. Thematic analysis was used, combining inductive identification of managerial challenges and a mapping exercise to locate these encounters against health system quality dimensions in the Australian National Health Performance Framework (NHPF). Results: Reported challenges to promoting and sustaining quality health care within RACFs included barriers to recruiting and retaining skilled staff, service constraints resulting from geographical isolation, limited access to quality fiscal resources, and a recent change to regulatory and administrative requirements. Identified challenges touch on all sub-dimensions of the NHPF. Conclusion: Several forces, many structural, currently challenge quality health care services in northern Queensland RACFs. Senior management teams come under substantial pressure and are developing short term solutions to protect quality in the face of often chronic and structural challenges. Alongside work to address macro-level issues, more work is needed to understand the personal and professional attributes of senior managers who are successful in positively influencing facility-level quality issues.